Docencia universitaria: al rescate del valor público - Muñoz G., Gabriela (Revista Hospital Clínico Universidad de Chile, 2009)
Superior Education is a fundamental area in our society, very often postponed without considering enough the urgent need of changes, even though discussion is persistent about its importance as essential instrument for developing citizenship, and a fair, consistent and coherent community. In our institutional setting, being such a teacher is a far distant model. A review of what is felt lacking in our environment to get the necessary human resource to recover the plain public wealth in health education and assistance. The most significant aspects to be covered are noted as: 1) - to keep good proportion between the opportunities of practical learning and consequent teaching, and the medical service provided by activities that may accomplish both goals. 2) - giving adequate stimulus to enhanced accessing and perform as a competent health professional and to become an outstanding health graduate. 3) - privileging programs for advanced though rational knowledge, under professionals criteria, which put emphasis in problems resolution and decision making better than in contingent and concrete abilities. 4) - give due relevance to autonomic practice; development of assertive, critical and “autopoietic” aptitudes; rely on humanistic and ethic procedures. 5) - support quality and dignity of the professions in values comprise in professionalism itself, conceived regulated by a safeguard of personal responsibility and suitable accreditation.